2016
DOI: 10.1007/s10792-016-0268-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pain experience during 23-G vitreoretinal surgery under topical and retrobulbar anesthesia

Abstract: The objective of this study is to compare pain and discomfort scores of patients during 23-G vitreoretinal surgery under topical and retrobulbar anesthesia without using sedation. A total of 157 patients with various vitreoretinal disorders were included in this study. Patients were randomly divided into two groups: topical (group 1, n = 76) and retrobulbar anesthesia (group 2, n = 81). Patients underwent 23-G vitreoretinal surgery without using sedation. All patients rated the level of experienced pain during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Regarding retrobulbar local anesthesia we had to wait for at least 10 to 20 minutes before the effect of anesthesia was achieved, whereas in case of topical local anesthesia, the onset was rapid and we could start surgery immediately. This clearly saves the time of surgeon [13][14][15] .…”
Section: Discussionmentioning
confidence: 88%
“…Regarding retrobulbar local anesthesia we had to wait for at least 10 to 20 minutes before the effect of anesthesia was achieved, whereas in case of topical local anesthesia, the onset was rapid and we could start surgery immediately. This clearly saves the time of surgeon [13][14][15] .…”
Section: Discussionmentioning
confidence: 88%
“…The initial electronic database search yielded 1501 articles after removal of duplicates, with 36 studies selected for full-text review (see Figure 1 for a PRISMA flow diagram). Excluded were 3 non-RCTs, 6,10,11 6 not full-length articles, 12 –17 1 article published before 1990, 18 16 studies with vitreoretinal surgery for other causes than retinal detachment, 19 –34 and 2 articles without vitreoretinal surgery. 35,36 The 8 remaining articles were included in this systemic review.…”
Section: Resultsmentioning
confidence: 99%
“…There are several reports of vitreoretinal surgery and combined phacoemulsification vitrectomy being performed under topical anesthesia [16, 21, 27-30]. Yepez et al [16, 17] reported that topical anesthesia, combined with neuroleptic anesthesia, was a safe and effective alternative to peribulbar or retrobulbar anesthesia in posterior vitrectomy procedures.…”
Section: Discussion/conclusionmentioning
confidence: 99%